Predicting Body Image Concern and Anxiety of Children based on Family Functioning and Communication Patterns of Parents of Students with Onychophagia - Rezaei NeJad Bakhtiyar, Mahnaz; Shahriari Ahmadi, Mansure (Shahroud Journal of Medical Sciences, 2025)
Background: Nail-biting can result in both physical and psychological consequences including emotional distress, anxiety, and depression. The study aimed to forecast the extent of concern regarding body image and anxiety in children by examining the family dynamics and communication styles of parents whose students have nail-biting habits in elementary schools in Tehran. Methods: The present study utilized descriptive and causal-correlational methodologies through regression analysis. The research participants are girls in the sixth grade who are enrolled in a primary school in the 6th district of Tehran in 2022, as well as their parents. 160 individuals were chosen through a combination of convenience and purposive sampling methods. The sample consisted of around 80 students and 80 parents. Data collection involved four standardized questionnaires related to The Body Image Concern Inventory, The Spence Children's Anxiety Scale-Parent Version (SCAS-P), The Communication Patterns Questionnaire (CPQ), and The McMaster Family Assessment Device (FAD). After collecting data, the study utilized descriptive statistics (age, gender, education level) and regression analysis. The data analysis was conducted using SPSS 23 software.Results: The findings showed a significant connection between family dynamics and body image concerns (Pvalue<0.01). The correlation coefficient of r=-0.736 indicates a strong negative relationship between students' body image concerns and family dynamics. Likewise, the study revealed a notable link between parents' communication styles and body image concerns (r=0.860). A greater emphasis on communication by parents is associated with a reduction in students' body image concerns, demonstrating a strong negative relationship between these factors (Pvalue<0.01). Conclusions: It is suggested that primary schools improve communication with parents of students who are dealing with anxiety, body image issues, and nail-biting habits to effectively help them overcome these challenges.